2013
DOI: 10.1021/ac400961b
|View full text |Cite
|
Sign up to set email alerts
|

Filter-Based Assay for Escherichia coli in Aqueous Samples Using Bacteriophage-Based Amplification

Abstract: This paper describes a method to detect the presence of bacteria in aqueous samples, based on the capture of bacteria on a syringe filter, and the infection of targeted bacterial species with a bacteriophage (phage). The use of phage as a reagent provides two opportunities for signal amplification: (i) the replication of phage inside a live bacterial host and (ii) the delivery and expression of the complementing gene that turns on enzymatic activity and produces a colored or fluorescent product. Here we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…Second, they allow for the separation of the bacteria from matrices like: milk, orange juice, turbid water and so on, that would otherwise interfere with colorimetric assays. 7,9 Smartphone-based technology has become increasingly more popularly for use in analytical diagnostics. Erickson and his co-workers developed a smartphone platform to quantify 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 vitamin D levels and detect pH change in saliva and sweat.…”
Section: Resultsmentioning
confidence: 99%
“…Second, they allow for the separation of the bacteria from matrices like: milk, orange juice, turbid water and so on, that would otherwise interfere with colorimetric assays. 7,9 Smartphone-based technology has become increasingly more popularly for use in analytical diagnostics. Erickson and his co-workers developed a smartphone platform to quantify 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 vitamin D levels and detect pH change in saliva and sweat.…”
Section: Resultsmentioning
confidence: 99%
“…We next used our enzyme‐induced metallization colorimetric assay to detect E. coli cells. β‐gal is an essential enzyme in the inducible lactose transport and metabolism system of E. coli , and can be used as an indicator for their presence . Because phages can distinguish between live and inactive bacteria, their use as detection probes reduces the possibility of false‐positive results .…”
Section: Resultsmentioning
confidence: 99%
“…5 Furthermore, phagefunctionalized surfaces can be used in biosensor designs using platforms such as surface plasmon resonance, 6-7 quartz crystal microbalance, 8 or dip-stick assays. 9 In an earlier study, we demonstrated the efficacy of a phage-functionalized surface for the capture and deactivation of bacteria. 10 The findings emphasized how the orientation of the immobilized phage, specifically the position of its host binding proteins on the surface, played a significant role in the capture of host bacteria.…”
Section: Thesis Objectivesmentioning
confidence: 98%